Implementation of PJBL-Based Worksheet with a STEAM Approach to Improve High School Students' Creative Thinking Abilities: A Synthesis of Empirical Insights - Nadya Mazayu Nur Sabrina; Budi Jatmiko (Journal of Digitalization in Physics Education, 2025)
Objective:  This research uses a literature review to analyze the implementation of PJBL-based LKPD with a STEAM approach to improve high school students' creative thinking abilities. Method: The research method used is a qualitative approach with a library study design. This method was carried out by searching for articles from various sources such as Google Scholar, Scopus, and so on, as well as national and international journal websites, totaling 10 articles. The data that has been obtained will be classified and studied in depth, and then authentic data will be analyzed. The data analysis used is critical. Results: So, it can be concluded that the STEAM approach integrated with Project Based Learning (PjBL) consistently improves students' creative and critical thinking skills in various subjects. This approach effectively facilitates understanding of concepts and encourages active student engagement. Using innovative teaching materials such as LKPD and e-LKPD based on STEAM-PjBL has also proven to be practical and efficient in improving the quality of learning. Novelty: This research is expected to provide valuable insights for educators in utilizing innovative teaching materials, such as LKPD and e-LKPD integrated with the STEAM-PjBL approach, to improve students' creative and critical thinking skills while encouraging active involvement in 21st-century education.